Strategy For Strengthening Institutional Capacity of Badan Penanggulangan Bencana Daerah (BPBD) in Garut District - Indra Kristia; Yaya Mulyana (Iapa Proceedings Conference, 2019)
Indonesia is a disaster-prone area, both due to geological disasters, climate change, and human activities which as a whole require prevention, preparedness, emergency response and recovery as disaster management or disaster management. These activities have been determined by various policies and the establishment of disaster management institutions and organizations. This research is directed at strengthening the institutional capacity of the Regional Disaster Management Agency in Garut Regency which has not been effective Research uses qualitative research methods with organizational case study approaches. Qualitative case study research is a research strategy in which researchers investigate carefully a program, event, activity, process, or group of individuals (Creswell, 2016: 23). The researcher collects complete information by using various procedures for collecting data based on a predetermined time. Research shows that many factors inhibiting the strengthening of BPPD institutional capacity in Garut Regency so that it is not effective are as follows: There is no training on disaster in the BPBD environment, routine training has not been programmed to improve the ability of BPBD employees, salary or wages rely on APBD and there have been delays in salary payments which results in low employee morale. The current recruitment system is only quantity fulfillment, not yet talking about quality. The incentive system is not specifically regulated for organizations that have a high escalation such as BPBD. The personnel is very limited so the BPBD head has difficulty using the personnel. The leader in the BPBD should not be the same as the head of the SKPD in general. Not yet functional staff who can become professionals in carrying out their duties. Therefore, changes in policies and legal regulations are needed, there is no change in policy and legal rules in the face of emergency response conditions. It is also necessary to reform the institutional system carried out at the time of the disaster, before the disaster. To overcome this, several strategic steps are needed.